Neither COVID-19, nor cryopreservation, prevented allogeneic product infusion: A report from the National Marrow Donor Program - Farhadfar, Nosha; Newman, Jeni; Novakovich, Jennifer; Barten, Jacklyn; Ndifon, Eric T.; Oakes, Jason; Cody, Meghann; Pham, Huy P.; Auletta, Jeffery J.; Miller, John P.; Devine, Steven M.; Stefanski, Heather E. (Frontiers in Immunology, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic in early 2020 has resulted in an unprecedented level of uncertainty and challenge for the stem cell donor registries. To address these challenges, rapid strategies were implemented by the National Marrow Donor Registry (NMDP) and its network partners. Herein, we aim to report the impact of the COVID-19 pandemic on the collection, utilization of grafts, and short-term outcomes of patients who received stem cell products from COVID-19 positive donors. Methods: NMDP data during early phase (March 1, 2020 through May 1, 2020) of the pandemic was compared to the later phase (March 1, 2021 through May 1, 2021). Odd ratios were calculated to determine the impact of the pandemic on graft sources requested by transplant centers (TCs). The Kruskal Wallis test was used to test the effect of pandemic on the disease indication, volume of searches, and the number of products not infused. Results: Although there was an initial decline in overall donor searches during the early phase of pandemic, these numbers increased reaching pre-pandemic levels during the later phase. Urgent malignant diseases remained the most common indication for transplant in 2021. The pandemic necessitated cryopreservation of stem cell products due to transportation restrictions as well as clinical uncertainties in managing the virus. Cryopreserved grafts remained the most common requested grafts throughout the pandemic. In the later phase of the pandemic, the total numbers of requests for fresh grafts increased, mostly due to increase in requests for fresh bone marrow (BM) grafts. As the pandemic continued, TCs became more accepting of cryopreservation, resulting in reduction of number of products not infused. Lastly, no short-term deleterious outcomes were noted among the patients who had stem cell products infused from a SARS-CoV-2 positive donor. Conclusion: Throughout the pandemic, the NMDP and TCs worked tirelessly to ensure that patients would receive lifesaving grafts when needed. The data reported here , although limited by small numbers, illustrate that transplantation from donors with COVID-19 is feasible and safe.